Organizational Development of Russian SMEs: Current trends - Velinov, Emil; Ponomarev, Maxim (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
The research paper sheds a light on Russian SMEs transition and specifically on their current development and evolution. The paper attempts to explain what are the main drivers and antecedents on SMEs during the period 2010-2015. Along with it, it is applied detailed analysis of Russian SMEs in terms of key performance indicators, turnover and volume of sales. Further, are given potential developments and trends within SMEs in Russia. The paper draws attention to socio-economic and political factors influencing SMEs development.